Geographic, clinical, serologic, and molecular evidence of granulocytic ehrlichiosis, a likely zoonotic disease, in Minnesota and Wisconsin dogs. - Greig, B (1996)
Seventeen Minnesota and Wisconsin dogs with granulocytic ehrlichosis were studied. The diagnoses were made by finding ehrlichia morulae in peripheral blood neutrophils. Eight dogs were studied retrospectively, and nine dogs were studied prospectively. The medical records of all dogs were reviewed. Eighty-eight percent of the dogs were purebred and 76% were spayed females. The median age was 8 years. Sixty-five percent of the cases were diagnosed in October and November. Fever and lethargy were the most common clinical signs. The most frequent laboratory findings were lymphopenia, thrombocytopenia, elevated activities of serum alkaline phosphatase and amylase, and hypoalbuminemia. No dogs seroreacted to Ehrlichia canis or Ehrlichia chaffeensis antigens, which are cross-reactive. Seventy-five percent of the dogs tested during the acute phase of disease and 100% of the dogs tested during convalescence were seropositive for E. equi antigens. Granulocytic ehrlichial 16S rRNA gene DNAs from six dogs were amplified by PCR. Sequence analysis of a 919-bp sequence of the ehrlichial 16S rRNA gene amplified by PCR from the blood of two dogs revealed the agent to be identical to the agent of human granulocytic ehrlichiosis in Minnesota and Wisconsin and to be very similar to E. equi and Ehrlichia phagocytophila and less similar to E. canis, Ehrlichia ewingii, and E. chaffeensis. The geographic, clinical, serologic, and molecular evidence indicates that granulocytic ehrlichiosis in Minnesota and Wisconsin dogs is not caused by E. ewingii, but suggests that it is a zoonotic disease caused by an agent closely related to E. equi and that dogs likely contribute to the enzootic cycle and human infection.